Avaliação da sensibilidade de mecanismos cinéticos químicos reduzidos para queima de etanol/gasolina na predição do fenômeno da detonação em um motor de combustão interna por simulações CFD 3D - Raphael Meireles Braga (2018)
With the increasing of pollutant emission restrictions by fossil fuel burning, the downsizing technology has become mandatory in modern internal combustion engines. However, keeping the engine operating at a high compression ratio, load and temperatures comes together with knocking issues. The computational fluid dynamics is a powerful tool that allows a better understanding of the phenomena that take place in the combustion chamber and it is an essential phase in the engine development process. In this context, the present dissertation presents a comparison of the capacity to characterize the knock phenomenon in a single cylinder spark ignition engine with different reduced chemical kinetics mechanisms for ethanol-gasoline blends oxidation. Therefore, a methodology for 3D numerical simulation of direct injection internal combustion engine is presented. Thus, a calibration and validation of KH-RT break up model constant is made by means of quiescent spray vessel simulations. In addition, the sensibility of combustion results in relation of the wall liquid film formation model is assessed for gasoline E27 as fuel and three models are used: ORourke, Bai-Gosman and Kuhnke. With the validated spray models, three chemical kinetic models (66, 75 and 115 species) are evaluated in an engine simulation with the engine velocity of 3000 rpm, 6 bar of break mean effective pressure and E10 as fuel both for maximum brake torque (MBT) spark time and for knock border spark timing condition. Knock indexes are calculated for each mechanism and compared with experimental values and the results show that none of the mechanism was able to correctly characterize knock in the engine, since maximum amplitude of pressure oscillations were roughly ten times the experimental value. Moreover, for the MBT case (non-knocking condition) the mechanisms predicted a slight trace of knock, which is not seen in the experimental test. At last the 75 species model is implemented in an engine case with a different fuel blend (gasoline E22) and presented much more satisfactory results